2020
DOI: 10.1007/s12355-020-00815-0
|View full text |Cite|
|
Sign up to set email alerts
|

Forecasting International Sugar Prices: A Bayesian Model Average Analysis

Abstract: This paper examines the relative importance of key variables for the prediction of international sugar prices. Understanding movements in world sugar prices helps policy-makers and participants in the sugar value chain to formulate effective investment strategies and forecast the effects of market shocks more accurately. We combine a Bayesian model averaging (BMA) technique to address specification uncertainty with an out-of-sample analysis to evaluate price predictability. Results show that world sugar quotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…However, Kuzmenko et al [38] revealed mutual interaction between selected stock exchanges and confirmed long-term equilibrium. Global sugar prices are recognised as highly volatile [40]; the volatility stems from the economic and physical characteristics of the sugar markets [41,42], as well as various support measures that benefit the subsector [43]. However, the international sugar agreement dissolution (1983) had a large impact on volatility, which resulted in an overnight drop in international sugar price by 38% [44].…”
Section: Introductionmentioning
confidence: 99%
“…However, Kuzmenko et al [38] revealed mutual interaction between selected stock exchanges and confirmed long-term equilibrium. Global sugar prices are recognised as highly volatile [40]; the volatility stems from the economic and physical characteristics of the sugar markets [41,42], as well as various support measures that benefit the subsector [43]. However, the international sugar agreement dissolution (1983) had a large impact on volatility, which resulted in an overnight drop in international sugar price by 38% [44].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the sugar prices, the results were very similar. It is expected that their prices will have stronger convergence with each other, including in the short term, given that Brazil is the largest global supplier and, therefore, its supply has a significant impact on international prices (Amrouk and Heckelei 2020 ). Rumánková et al ( 2019 ) found evidence that the main international sugar prices, such as New York and London, despite their regional differences and technical specificities, have a significant interrelationship, with Brazil and India as key players in this interdependence due to their supply capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…The literature on modeling international sugar markets and projecting their prices tends to use general equilibrium models [6] or partial equilibrium models [15][16][17]. These are usually recursive approaches that provide annual market balances for production, consumption, trade, and world prices over a projection period.…”
Section: Introductionmentioning
confidence: 99%